A Three-Dimensional (3D) Environment to Maintain the Integrity of Mouse Testicular Can Cause the Occurrence of Meiosis - Zhi-li CHU; Chao LIU; Yao-fu BAI; Hai-jing ZHU; Yue HU; Jin-lian HUA (Journal of Integrative Agriculture, 2013)
Adhesions between different cells and extracellular matrix have been studied extensively in vitro, but little is known about their functions in testicular tissue counterparts. Spermatogonia and their companion somatic cells maintain a close association throughout spermatogenesis and this association is necessary for normal spermatogenesis. In order to keep the relative integrity of the testicular tissues, and to detect the development in vitro, culture testicular tissues in a three-dimensional (3D) agarose matrix was examined. Testicular tissues isolated from 6.5 d postpartum (dpp) mouse were cultured on the top of the matrix for 26 d with a medium height up to 4/5 of the 3D agarose matrix. The results showed that in this 3D culture environment, each type of testicular cells kept the same structure, localization and function as in vivo and might be more biologically relevant to living organisms. After culture, germ cell marker VASA and meiosis markers DAZL and SCP3 showed typical positive analysed by immunofluorescence staining and RT-PCR. It demonstrated that this 3D culture system was able to maintain the number of germ cells and promote the meiosis initiation of male germ cells.